New Developments and Future Trends in Low-Temperature Hot Stamping Technologies: A Review - Chenpeng Tong; Qi Rong; Victoria A. Yardley; Xuetao Li; Jiaming Luo; Guosen Zhu; Zhusheng Shi (Metals, 2020)
Improvement of the hot stamping process is important for reducing processing costs and improving the productivity and tensile properties of final components. One major approach to this has been to conduct all or part of the process at lower temperatures. The present paper reviews the state of the art of hot stamping techniques and their applications, considering the following aspects: (1) conventional hot stamping and its advanced developments; (2) warm stamping approaches in which complete austenitisation is not attained during heating; (3) hot stamping with a lower forming temperature, i.e., low-temperature hot stamping (LTHS); (4) advanced medium-Mn steels with lower austenitisation temperatures and their applicability in LTHS. Prospects for the further development of LTHS technology and the work required to achieve this are discussed.